Does market structure matter on banks’ profitability and stability? Emerging vs. advanced economies - Mirzaei, Ali; Moore, Tomoe; Liu, Guy (Journal of Banking & Finance, 2013)
We empirically investigate the effects of market structure on profitability and stability for 1929 banks in 40 emerging and advanced economies over 1999–2008 by incorporating the traditional structure-conduct-performance (SCP) and relative-market-power (RMP) hypotheses. We observe that a greater market share leads to higher bank profitability being biased toward the RMP hypothesis in advanced economies, yet neither of the hypotheses is supported for profitability in emerging economies. The SCP appears to exert a destabilising effect on advanced banks, suggesting that a more concentrated banking system may be vulnerable to financial instability, however, the RMP seems to perform a stabilising effect in both economies. Evidence also highlights that profitability and stability increase with an increased interest-margin revenues in a less competitive environment for emerging markets. Overall, these results suggest that although policy measures to promote competition may dampen economic rent, excessive implementation may have an undesired destabilising impact on banks.